Embolization of tumor cells is rare in patients with systemic cancer and cerebral large vessel occlusion. (10th July 2020) - Wolpert, F.; Kulcsár, Z.; Hänsel, M.; Rushing, E.; Seystahl, K.; Schweizer, J.; Roth, P.; Luft, A.R.; Wegener, S.; Weller, M.
Abstract : Background and purpose: Stroke is a dreaded complication in patients with cancer. Besides paraneoplastic coagulopathy, chemotherapy, radiotherapy and tumor‐directed invasive procedures, circulating cancer cells may contribute to thrombus formation and embolic stroke. However, the incidence of tumor cells within the blood clots of cancer patients with stroke is unknown and the role of circulating tumor cells in the formation of cerebrovascular thrombi remains unclear. Methods: All patients who had undergone cerebrovascular thrombectomy at the University Hospital Zurich between 2014 and 2017 were screened for history of cancer. Clinical information was retrieved from the local stroke registry and the electronic charts and thrombi underwent a thorough histopathological re‐review. Results: Thirty‐two of 182 patients (18%) with thrombectomy had a history of cancer. The majority of patients had advanced stage cancer. However, even after extensive histopathological re‐review, only one specimen revealed tumor cells in the thrombus: a 75‐year‐old patient with acute occlusion of the middle cerebral artery who had been diagnosed with non‐small‐cell lung cancer 8.1 months prior to stroke. Conclusions: The presence of cancer cells in clots from cerebrovascular thrombectomy, indicative of a direct involvement of circulating tumor cells in the causation of stroke, is rare.